2014
DOI: 10.1111/febs.13169
|View full text |Cite
|
Sign up to set email alerts
|

α‐sarcin and RNase T1 based immunoconjugates: the role of intracellular trafficking in cytotoxic efficiency

Abstract: Toxins have been thoroughly studied for their use as therapeutic agents in search of an improvement in toxic efficiency together with a minimization of their undesired side effects. Different studies have shown how toxins can follow different intracellular pathways which are connected with their cytotoxic action inside the cells. The work herein presented describes the different pathways followed by the ribotoxin a-sarcin and the fungal RNase T1, as toxic domains of immunoconjugates with identical binding doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 68 publications
(96 reference statements)
0
33
0
Order By: Relevance
“…The mechanism of action of ITs includes the binding of its target region to the tumor‐associated antigen (TAA), internalization of the complex through receptor‐mediated endocytosis, and subsequent release of toxic regions that can lead to the death of target cells 4,24 . Therefore, the antitumor effect of ITs depends on several factors: the affinity of Abs for TAA expressed on the cell surface, the rate of internalization of the complex, and the inherent efficacy and specificity of the toxin 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of ITs includes the binding of its target region to the tumor‐associated antigen (TAA), internalization of the complex through receptor‐mediated endocytosis, and subsequent release of toxic regions that can lead to the death of target cells 4,24 . Therefore, the antitumor effect of ITs depends on several factors: the affinity of Abs for TAA expressed on the cell surface, the rate of internalization of the complex, and the inherent efficacy and specificity of the toxin 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of an immunotoxin depends on many molecular aspects, such as the antigen binding affinity, internalization rate, intracellular processing, toxin release and intrinsic toxicity. Accordingly, the intracellular trafficking of ribotoxin-based immunotoxins has been studied, showing how they are internalized via early endosomes, following different pathways depending on the toxin used until they reach the cytosol [ 13 , 75 ]. Finally, a step further in the therapeutic use of ribotoxin-based immunotoxins has been done showing the efficiency of the α-sarcin-based immunotoxin IMTXA33αs, which inhibits tumor growth as well as angiogenesis in nude mice harboring colon cancer xenografts [ 14 ] ( Figure 4 B).…”
Section: The Potential Biotechnological Uses Of Fungal Ribotoxinsmentioning
confidence: 99%
“…). Previous studies with other immunoconjugates based on scFvA33 have revealed how, when fused to RNaseT1, they follow a pathway via lysosomes and the Golgi apparatus, whereas, when using α‐sarcin, the immunotoxin is only internalized via the Golgi apparatus . In the case of IMTXA33HtA3ΔW, the immunotoxin follows a pathway involving both systems, as shown by the confocal microscopy assays (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Colocalization of IMTXA33HtA3DW with both the Golgi and lysosomes was observed ( Fig. 6), which would affect release to the cytosol, as described for scFvA33 immunoconjugates based on a-sarcin and RNase T1 [27]. IMTXA33HtA3DW showed specific cytotoxicity against GPA33-positive cells with an IC 50 of approximately 0.5 lM (Fig.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation